Back to the Future: A Green Industrial Policy for the Philippines - Ofreneo, Rene E. (Philippine Journal of Labor and Industrial Relations; Vol 32 No 1&2 (2012): Philippine Journal of Labor and Industrial Relations, 2021)
The Philippines is facing two major economic sustainability problems: 1) an economy with an eroding agricultural and industrial base; and 2) the nation’s extreme vulnerability to risks associated with environmental degradation and climate change. These twin challenges require a bold re-thinking of the country’s growth and development strategy in favor of one that promotes both accelerated industrial development and greener economy. For the first, the paper argues the need to replace the existing neo-liberal development framework with a forward-looking Industrial Policy. For the second, the paper argues that the Industrial Policy should be developed around the huge job and development potentials of greening a brown economy and degraded environment. However, to make the Green Industrial Policy work, the paper calls for economic-environmental-educational policy coherence as well as decisiveness on the part of the national leadership to pursue a policy break from the existing neo-liberal economic policy regime and neglect of the environment.